Studies On Aeromonas Hydrophila Isolated From Epizootic Ulcerative Syndrome (Eus) Positive Fish In Malaysia - Kulathilaka, H . A . Mahinda (1993)

(untitled)
The present study indicates that the only portal of entry of A . hydrophila serovar I isolate V which induces EUS - l ike lesions in C. batrach us is the intramuscular injection and the effective dose is 6 .5 X 1 0 6 CFU / fish . The lesions do not develop into putrefied necrotic ulcers but heals gradually within 14 - 18 days of initial injection . Immersion exposure and oral administration of A . hydrophila serovar I isolate V were incapable of inducing EUS - like lesions in C . batrachus .Intramuscular injection of A . hydrophila serovar I strain V cause severe pathological changes in C . batrachus , only at the site of injection and did not produce systemic infection . Clarias batrachus mounts a strong inflammatory response against A.hydrophila following intramuscular infection and is capable of eliminating bacteria from the infected tissue s and efficient in fast wound healing and repair of the dermal lesions.